2015
DOI: 10.1002/lt.24343
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Achilles' heel of adult living donor liver transplant: Corner‐sparing sutures with mucosal eversion technique of biliary anastomosis

Abstract: Biliary complications are regarded as the Achilles' heel of liver transplantation, especially for living donor liver transplantation (LDLT) due to smaller, multiple ducts and difficult ductal anatomy. Overall biliary complications reported in most series are between 10% and 30%. This study describes our modified technique of biliary anastomosis and its effects on incidence of biliary complications. This was a single‐center retrospective study of 148 adult LDLT recipients between December 2011 and June 2014. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…While identification of the causative factors of biliary complications and subsequent refinements in reconstruction techniques might reduce the incidence of these complications in some institutions [20][21][22], the rate of biliary complications, particularly biliary strictures, does not seem to significantly decrease with experience [7,8,19,23]. Kyoto University divided LDLT recipients into three groups according to case experience (Group 1, cases 1-100; Group 2, cases 101-200; and Group 3, cases 201-335), and found that while the rate of bile leakage significantly decreased with experience (25% in Group 1, 14% in Group 2, and 13% in Group 3, p = 0.021), there were no differences in the development of biliary strictures among the three groups (19,28, 26%, respectively, p = 0.290) [7].…”
Section: Incidence and Risk Factors Of Biliary Strictures After Ldltmentioning
confidence: 99%
“…While identification of the causative factors of biliary complications and subsequent refinements in reconstruction techniques might reduce the incidence of these complications in some institutions [20][21][22], the rate of biliary complications, particularly biliary strictures, does not seem to significantly decrease with experience [7,8,19,23]. Kyoto University divided LDLT recipients into three groups according to case experience (Group 1, cases 1-100; Group 2, cases 101-200; and Group 3, cases 201-335), and found that while the rate of bile leakage significantly decreased with experience (25% in Group 1, 14% in Group 2, and 13% in Group 3, p = 0.021), there were no differences in the development of biliary strictures among the three groups (19,28, 26%, respectively, p = 0.290) [7].…”
Section: Incidence and Risk Factors Of Biliary Strictures After Ldltmentioning
confidence: 99%
“…The incidence is higher after LDLT compared to deceased donor liver transplant (DDLT) [3] . Over last 3 decades the reported incidence of bile leaks as well strictures is decreasing (Table 1) [4][5][6][7][8][9][10][11][12][13][14][15] . This can be ascribed to better understanding of the technical causes leading to biliary complications.…”
Section: Magnitude Of the Problem And Contributing Factorsmentioning
confidence: 99%
“…Overview of the possible contributory factors and role of each has been listed in Table 2 [12, [14][15][16][17][18][19][20][21][22] . In LDLT the anastomosis is made between right anterior and posterior ducts of the donor with the common hepatic duct of the recipient.…”
Section: Magnitude Of the Problem And Contributing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The incidence of biliary complications at these centers is similar. (1) All the points raised in the letter might be theoretically relevant but probably have no practical implication. …”
mentioning
confidence: 99%